Barisan Nasional's GE14 campaign materials: a reversed third-person effect - Syed Abdullah Idid, Syed Arabi; Souket, Rizwanah (Taylor's University Lakeside Campus, 2019)
The third-person effect theory postulates that respondents would deny media’s direct effect on themselves but would perceive the same media as having a greater effect on others. A “reverse” third-person effect happens when the intended influence is perceived to be desirable or intelligent on oneself. This perception is sometimes referred to as the “first-person” effect claiming that people perceive greater communication influence on themselves than on others. The third-person effect has been studied on cross sections of populations but it is not clear what the effects would be if examined on a longitudinal basis. Applying this paradigm to the Malaysian voter scenario in the 2013 general elections, Idid and Souket (2014) studied the influence of Barisan Nasional’s (BN) political campaign literature on BN voters under two categories- “self” which included themselves, their family, and like party supporters and “others” that included opposition supporters and undecided voters. The study found that BN supporters displayed a positive confidence on the influence of BN’s campaign materials on self (88%) and on others (77%). Hence, a reversed thirdperson effect, that is, a first-person effect was observed for the perceived level of influence of BN’s political communication materials on BN voters. This finding was attributed to the confidence and positive sentiment of BN voters towards their own party communication materials, finding the materials desirable and favourable. The present study investigated the effect of BN’s political campaign literature on BN voters and opposition voters in the recent 2018 general election. The findings of Idid and Souket (2014) study on the 2013 election were then compared to the current study. The study posits that voter confidence is an important factor in predicting voter influence and perceived effect on others that may result in a third-person effect or a reversed third-person effect given two different contextual situations. This longitudinal study addresses the issue of the third person effect during the periods when BN was strong (2013) and when it lost its dominant position in Malaysian politics (2018).